Development of ULOS Learning Model with AR to Foster Cultural Appreciation - Sijabat, Apriani; Festiyed, Festiyed; Razak, Abdul; Diliarosta, Skunda; Lufri, Lufri; Leonie, Natasha (Pandawan, 2025)
Indonesia is rich in diverse cultural heritage, including the traditional ULOS cloth from North Sumatra. To preserve and appreciate local culture, it is essential for student teachers to develop a deep understanding and love for that culture. The ULOS-based learning model, assisted by Augmented Reality (AR), is designed to achieve this goal. This research aims to develop a learning model based on the Project-Based Learning (PjBL) model, referred to as the ULOS model, to increase cultural understanding and appreciation among prospective teacher students. The study follows a Research and Development approach using the ADDIE development model. The sample includes elementary school teacher education students from UHKBPNP during the trial and effectiveness testing stages. Data collection involved expert validation sheets to assess the model suitability and test instruments to measure students love for their culture. The results demonstrate that the ULOS learning model assisted by AR, was declared valid, effective, and practical. It significantly enhanced students understanding of Batak culture and ULOS cloth, while also increasing their positive attitudes and love for local culture. The use of ULOS cloth as a teaching aid not only enriches the learning process but also strengthens cultural identity and fosters pride in Indonesia cultural heritage. The ULOS learning model is effective in enhancing cultural understanding and appreciation and has the potential to be adopted and developed in various educational and cultural contexts worldwide.